Antimicrobial properties of extracts Vexibia alopecuroides (Experimental biology, 2016)
Microorganisms Staphylococcus aureus ATCC 29213, Methicillin-resistant S. aureus ATCC 43300, Pseudomonas aeruginosa ATCC 27853, Candida albicans ATTC 90028, Candida krusei ATCC 6258, Candida glabrata ATTC 90030 was used to determine the antimicrobial activity of dichloromethane extracts and alcohol by serial dilution. The extracts were isolated from roots of Vexibia alopecuroides. Samples were collected in the flowering phase in the Almaty region. High antibacterial activity of the extract dichloromethane (concentration of half-maximal inhibition of 3 mg / ml) against Staphylococcus aureus and methicillin - resistant Staphylococcus aureus and the antagonistic effect of biologically active substances in its composition in relation to the yeast Candida Albicans ATTC 90028, Candida krusei ATCC 6258, Candida glabrata ATCC 90030.
Keywords: total extracts; fraction; antimicrobial activity.